Individual patient data analysis of the BIOFLOW study program comparing safety and efficacy of a bioresorbable polymer sirolimus eluting stent to a durable polymer everolimus eluting stent. Issue 5 (5th September 2020) - Toelg, Ralph; Slagboom, Ton; Waltenberger, Johannes; Lefèvre, Thierry; Saito, Shigeru; Kandzari, David E.; Koolen, Jacques; Richardt, Gert
Abstract: Objectives: This analysis of pooled individual patient data (IPD) aimed to evaluate the safety and efficacy of a bioresorbable polymer sirolimus eluting stent system (BP‐SES; Orsiro) compared to a durable polymer everolimus eluting stent system (DP‐EES; Xience) in the pooled population as well as in subgroups. Methods: IPD with up to 12 months follow‐up of the randomized controlled trials BIOFLOW‐II (NCT01356888), ‐IV (NCT01939249), and ‐V (NCT02389946) as well as the all comers registry BIOFLOW‐III (NCT01553526) were pooled. A total of 3, 717 subjects (2, 923 in BP‐SES and 794 in DP‐EES) with 5, 328 lesions (4, 225 lesions in BP‐SES and 1, 103 in DP‐EES) were included in the IPD. The primary endpoint was target lesion failure (TLF) at 12 months follow‐up. Subgroups analyzed included diabetes, age (≥65 years), gender, complex lesions (B2/C), small vessels (reference vessel diameter ≤2.75 mm), multivessel treatment, renal disease, and patients with acute coronary syndrome. Results: Overall, TLF at 12 months was significantly lower with 5.2%in the BP‐SES group versus 7.6% in the DP‐EES group ( p  = .0098). Similarly, target vessel myocardial infarction (TV‐MI) was 3.1 versus 5.7% ( p  = .0005). The rate of stent thrombosis was similar in both groups (0.004%). By regression analysis, an independent stent effect in favor of BP‐SES was observed for TLF ( p  = .0043) and TV‐MI ( p  = .0364) in small vessels. Conclusion: Results of this IPD analysis suggest that the BP‐SES with ultrathin struts is as safe as and more efficacious than DP‐EES in the overall cohort and especially in small vessels.